STIMULASI AKAR STEK PUCUK PELAWAN MERAH (Tristaniopsis marguensis Griff.) DENGAN PEMANFAATAN HORMON SINTESIS DAN ALAMI - Janaria, Siti; Setyaningsih, Luluk; Hasibuan, Ratna Sari; Setiawan, Dedi (Universitas Nusa Bangsa, 2023)
Red Pelawan (Tristaniopsis merguensis Griff.) Peter G. Wilson & J. T. Waterh is a member of the Myrtaceae family. This plant is widely spread in the forests of the Bangka Belitung Islands. This study aims to determine the success of Pelawan propagation by cuttings using a mixture of cocopeat, rice husk and rice husk charcoal as well as the application of synthetic and natural growth regulators (shallot extract). This study was designed using a factorial complete randomized design with the type of media and the type of growth regulator as the factors. Cutting material in the form of shoots, 6-10 cm in size, from a 2 - 4 years old pelawan tree in Pelawan Forest, Central Bangka. Synthetic hormones used the commercial brand Root-Up with a concentration of 15 g/10 ml, and natural hormones used shallot extract with a concentration of 200 g/300 ml of water. The results showed that the use of the two media did not have a significantly different effect, except for the percentage of surviving cuttings. Within 3 months of observation, the aplication of natural hormones, shallots, the cuttings which were able to root reached 4% with a root length of 16.5 mm, and to be sprouted as much as 2% with a shoot length of 5.5mm. Although the growth of cuttings treated with shallots was significantly lower than cuttings treated with synthetic hormones, the survival rate of cuttings reached 68% with shallot hormone treatment, indicating that shallots have the potential as an alternative natural hormone to stimulate the growth of T. merguensis cuttings.